2018
DOI: 10.1590/s1983-41952018000400007
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the effect of partial interaction in the evaluation of the effective width of composite beams

Abstract: Most of the engineering problems involving structural elements of steel-concrete composite beam type are approximations of the structural problem involving concrete plates connected by connectors to steel beams. Technical standards allow the replacement of the concrete plate element by a beam element by adopting a reduction in the width of the plate element known as effective width. The effective width is obtained, in most technical norms, taking into account only the parameters of beam span length and distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…These include, for example, different mechanical properties and independent stress-strain relation-ships. For other characteristics and more details of the flat shell element, consult Huang et al (1999Huang et al ( , 2003aHuang et al ( , 2003b and Silva and Dias (2018a).…”
Section: Flat Shell Elementmentioning
confidence: 99%
See 1 more Smart Citation
“…These include, for example, different mechanical properties and independent stress-strain relation-ships. For other characteristics and more details of the flat shell element, consult Huang et al (1999Huang et al ( , 2003aHuang et al ( , 2003b and Silva and Dias (2018a).…”
Section: Flat Shell Elementmentioning
confidence: 99%
“…In the definition of the internal force vector and tangent stiffness matrix, it is assumed that the displacements and rotations have quadratic variations along the element and can be written in terms of the nodal displacements. For details on how to obtain the numerical formulation of this element, consult Silva and Dias (2018a).…”
Section: Flat Shell Elementmentioning
confidence: 99%
“…These elements were pre-dimensioned according to the recommendations of AASHTO (2017). Furthermore, research has shown that the main parameters that influence the effective width are the slab height, span length, load type and application, the distance between beams and webs in the cross section and the steel-concrete interaction degree (Castro et al, 2007;Dezi et al, 2006;Gara et al, 2011;Hu et al, 2009;Reginato et al, 2018;Silva and Dias, 2018;Yuan et al, 2016;Zhu et al, 2015). Therefore, the parametric analysis variables were:…”
Section: Parametric Analysismentioning
confidence: 99%
“…The shear lag effect has been investigated by several authors who developed equations for determining the effective width of slabs in steel-concrete composite beams (Abbu et al, 2014; Amadio and Fragiacomo, 2002; Castro et al, 2007; Gara et al, 2011b; Lasheen et al, 2018; Reginato et al, 2018; Silva and Dias, 2018; Yuan et al, 2016; Zhu et al, 2015). It is worth mentioning the work of Abbu, Ekmekyapar and Ozakça (2014) that addressed steel-concrete composite bridges specifically in the box section configuration; and the research by Yuan et al (2016) and Zhu et al (2015), who investigated steel-concrete composite bridges and proposed expressions to determine the effective width.…”
Section: Introductionmentioning
confidence: 99%
“…Acta Scientiarum. Technology, v. 46, e64764, 2024 In the context of steel-concrete composite bridges, the effective width is a widely studied topic (Dezi, Gara, & Leoni, 2003;Amadio, Fedrigo, Fragiacomo, & Macorini, 2004;Chiewanichakorn, Aref, Chen, & Ahn, 2004;Macorini, Fragiacomo, Amadio, & Izzuddin, 2006;Gara, Leoni, & Dezi, 2009;Gara, Ranz i, & Leoni, 2011;Salama & Nassif, 2011;Wang & Nie, 2015;Zhu, Nie, Li, & Ji, 2015a;Galuppi & Royer -Carfagni, 2016;Yuan, Deng, Yang, Weijian, & Zhenggeng, 2016a;Reginato, Tamayo, & Morsch, 2018;Lasheen, Shaat, & Khalil, 2018;Silva, & Dias, 2018;Nicoletti et al, 2021a;2021b). One of the justifications for the high number of researches is the fact that the effective width is a parameter that directly influences the design of these structures.…”
Section: Introductionmentioning
confidence: 99%